Sociological Analysis of Javanese Culture in The Novel Nyai Gowok by Budi Sardjono - Laila Tri Lestari; Yessy Soniatin; Ala Imroatana; Elva Isna Maulidyah (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2020)
Through his novel, Nyai Gowok , Budi Sardjono describes aspects of Javanese culture. This research focuses on two problems, namely: (1) the function of literature and (2) the literary values ​​contained in the novel Nyai Gowok by Budi Sardjono. The approach used in this study is a qualitative descriptive approach. The data in this study are excerpts of novels related to the function of literature and also the values ​​in literature which include moral values, social values, and also the spiritual values ​​of Javanese society. While the data source is in the novel entitled Nyai Gowok , Budi Sardjono. Collecting data in this study using library, listening, and note-taking techniques, collecting and selecting data according to the research objectives, and combining them with the relevant theories. To analyze it, the writer uses the steps of (1) rereading carefully the results of the notes that have been obtained in the field, (2) classifying, (3) rereading the literature related to the relevant study problems that need to be done. Based on the analysis in the data, the results of this study are (1) the literary functions that exist in the novel entitled Nyai Gowok , by Budi Sardjono which describes the literary functions of the novel (2) the literary values ​​in Javanese society that exist in